Genotyping of tick-borne encephalitis and Kemerovo viruses in taiga ticks collected in the Komi Republic - Kartashov, M. Yu; Mikryukova, T. P.; Krivosheina, E. I.; Kuznetsov, A. I.; Glushkova, L. I.; Korabel`nikov, I. V.; Egorova, Yu. I.; Ternovoi, V. A.; Loktev, V. B. (Infekt͡s︡ii͡a︡ i immunitet, 2020)
Over the last years, an increasing rate of ixodes tick bites has been registered in the northern regions of the European Russia. In addition, the number of subjects request medical assistance due to tick bites has been dramatically increased in the Komi Republic. In addition, incidence of tick-borne encephalitis was also increased particularly starting since 2009. However, highly limited data on pathogen genetic diversity related to viral tick-borne infections in this region are currently available. Taiga ticks (Ixodespersulcatus) collected from the Komi Republic southern and central part vegetation were examined to identify and genotype tick-borne viruses. Individual ticks were used to identify by RT-PCR viral RNA coupled to tick-borne encephalitis and Kemerovo viruses. Viral genome fragment sequencing allowed to unambiguously identify these viruses. It was found that viral RNA tick-borne encephalitis was detected in 6.8±1.2% individual ticks. Moreover, tick-linked isolate genotyping based on analyzing E protein gene fragment nucleotide sequence derived from tick-borne encephalitis discovered that 35% and 65% isolates belonged to the Far Eastern and Siberian subtype, respectively. In addition, subsequent phylogenetic analysis demonstrated that at least four variants of the Siberian and Far Eastern subtypes of tick-borne encephalitis virus were detected, which were close to the viruses circulating in the Urals and Siberia. In contrast, prevalence of Kemerovo virus in taiga ticks was 0.8±0.2%. Sequencing of Kemerovo virus RNA-dependent RNA polymerase gene fragment showed around 94% homology with the remainder of the Kemerovo virus strains. Phylogenetic analysis of the Kemerovo virus genome fragments demonstrated at least two subtypes circulating in the Komi Republic. Thus, it was suggested that tick-borne encephalitis virus was introduced relatively recently from the Urals and Siberian region into the natural foci of the Komi Republic. Moreover, genetic differences found in Kemerovo virus strains presume for them a longer lasting evolution throughout the natural foci of this region. In addition, a potential role for birds and their ticks in rapid spreading of viral tick-borne infections in the Komi Republic is also discussed. Thus, the data on genetic diversity of the viral agents related to tick-born encephalitis and Kemerovo fever may be useful for improving their diagnostics, prevention and treatment in the Komi Republic.